Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 96463 species occurrences available in GBIF matching the query: { "Geometry" : [ "POLYGON((-117.266693 32.757252,-117.266693 32.659609,-117.210388 32.659609,-117.210388 32.757252,-117.266693 32.757252))" ] } The dataset includes 96463 records from 65 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0000220-150528172251762/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences